A) |x+22|-|4x+8|, X E (- nieskonczonosc, -2)
b)|3x-6|-|x-2|, x E<2, + nieskonczonosc)
c)3|x-3|-|6-2x|, x mniejsze albo rowne 3
d)2|x+1|-|3+3x|, x wieksze albo rowne -1
e)|x+2|-|x-1|, X E (-2, 1)
f)|x-3|-|x+4|, x E(-4, 3)
g) |2-x|+|3x+1|-2x, xE (- 1/2, 2)
h) 4x-|3+x|-|x+1|. xE (- nieskonczonosc, -3)

1

Odpowiedzi

  • Roma
  • Community Manager
2010-01-15T04:36:25+01:00
A) |x+22|-|4x+8|, x∈(- ∞, -2)
dla x < -22
x+22 < 0, więc |x+22| = -(x+22)
4x+8 < 0, więc |4x+8| = -(4x+8)
|x+22|-|4x+8| = -(x+22) + (4x+8) = -x - 22 + 4x + 8 = 3x - 14
dla -22 ≤ x < -2
x+22 ≥ 0, więc |x+22| = x+22
4x+8 < 0, więc |4x+8| = -(4x+8)
|x+22|-|4x+8| = x+22 + (4x+8) = x + 22 + 4x + 8 = 5x + 30

b)|3x-6|-|x-2|, x∈[2, + ∞)
dla x ≥ 2
3x - 6 ≥ 0, więc |3x - 6| = 3x - 6
x - 2 ≥ 0, więc |x - 2| = x - 2
|3x - 6| - |x - 2| = 3x - 6 - x + 2 = 2x - 4

c) 3|x-3|-|6-2x|, x ≤ 3
dla x = 3
3|x-3|-|6-2x| = 0
dla x< 3
x - 3 < 0, więc |x-3| = -(x - 3)
|6 - 2x| > 0, więc |6-2x| = 6 - 2x
3|x - 3|-|6 - 2x| = 3*(-x + 3) - (6 - 2x) = -3x + 9 - 6 + 2x = -x + 3

d) 2|x+1|-|3+3x|, x ≤ -1
dla x = -1
2|x+1|-|3+3x| = 0
dla x < -1
x + 1 < 0, więc |x +1| = -(x + 1)
3 + 3x < 0, więc |3 + 3x| = -(3 + 3x)
2|x + 1|-|3 + 3x| = 2*(-x - 1) + (3 + 3x) = -2x - 2 + 3 + 3x = x + 1

e) |x+2|-|x-1|, x ∈(-2, 1)
dla -2 < x < 1
x + 2 > 0, więc |x + 2| = x + 2
x - 1 < 0, więc |x - 1| = -(x - 1)
|x + 2| - |x - 1| = x + 2 +(x - 1) = x + 2 + x - 1 = 2x + 1

f) |x-3|-|x+4|, x ∈ (-4, 3)
dla -4 < x < 3
x - 3 < 0, więc |x - 3| = -(x - 3)
x + 4 > 0, więc |x + 4| = x + 4
|x - 3| - |x + 4| = -(x - 3) - (x + 4) = -x + 3 - x - 4 = -2x -1

g) |2-x|+|3x+1|-2x, x∈ (-½, 2)
dla -½ < x < -⅓
2 - x > 0, więc |2 - x| = 2 - x
3x + 1 < 0, więc |3x + 1| = - (3x + 1)
|2 - x| + |3x + 1| - 2x = 2 - x - 3x - 1 - 2x = -6x + 1
- ⅓ ≤ x < 2
2 - x > 0, więc |2 - x| = 2 - x
3x + 1 > 0, więc |3x + 1| = 3x + 1
|2 - x| + |3x + 1|- 2x = 2 - x + 3x + 1 - 2x = 3

h) 4x-|3+x|-|x+1|. x∈ (- ∞, -3)
dla x < - 3
3 + x < 0, więc |3 + x| = -(3 + x)
x + 1 < 0, więc |x + 1| = -(x + 1)
4x - |3 + x| - |x + 1| = 4x + (3 + x) + (x + 1) = 4x + 3 + x + x + 1 = 6x + 4